Views on Cultural Diversity as well as Authoritarian and Ethnocentric Attitudes of Russians - Dmitry Sergeevich Grigoryev (Peoples' Friendship University of Russia (RUDN University), 2020)
The article considers the relationship of different views on ethnocultural diversity (intergroup ideologies) and authoritarian and ethnocentric attitudes of Russians. This is an important issue because, having the status of a culturally dominant group, it is the ethnic Russians who largely determine the mutual character of intercultural relations in Russia. In this regard, an empirical study was carried out aimed at (1) testing the relationship of intergroup ideologies (assimilationism, colorblindness, multiculturalism, polyculturalism) with other attitudes relevant to intercultural relations (ethnocentrism, right-wing authoritarianism, social dominance orientation) and (2) testing their sociofunctional orientation. A cross-sectional one-sample correlation design using data from the socio-psychological survey was applied. According to the results of the study on a sample of 225 ethnic Russians, it was found that: (1) assimilationism was positively associated with intergroup ethnocentrism; (2) colorblindness was negatively associated with intragroup and intergroup ethnocentrism, authoritarian aggression, conventionalism as well as dominance and anti-egalitarianism; (3) multiculturalism was positively associated with intragroup ethnocentrism and conventionalism; and (4) polyculturalism was negatively associated with intergroup ethnocentrism. In addition, it was proposed to distinguish four dimensions of the considered attitudes for a general description of intercultural relations in Russia: (1) protective group motivation aimed at collective security and cohesion (intragroup ethnocentrism and right-wing authoritarianism); (2) social domination orientation (dominance and anti-egalitarianism); (3) cultural dominance orientation and superiority (intergroup ethnocentrism, assimilationism and rejection of colorblindness); and (4) acceptance of cultural diversity (multiculturalism and polyculturalism). The results were discussed in terms of the importance of taking into account the historical development of intercultural relations in Russia.